1976
DOI: 10.1007/bf00312873
|View full text |Cite
|
Sign up to set email alerts
|

Spastic paraplegia associated with addison's disease: Adult variant of adreno-leukodystrophy

Abstract: Clinical and pathological features of an adult variant of adreno-leukodystrophy (ALD) are presented. A male with clinical and laboratory signs of Addison's disease (AD) developed at age 22 a slowly progressing paraplegia with slight sensory deficits in both legs and bladder and sphincter dysfunctions; he died at age 24 in an AD crisis. Autopsy revealed hyperplasia of lymphatic tissues, lymphocytic infiltrates in various organs including the CNS and adrenocortical atrophy with prominence of large ballooned, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…At least three patients (D, I and Z) reported that the characteristic sparse scalp hair had already manifested itself before puberty. In fact, in the very ®rst report of a patient with AMN, ®rst areolar, then diffuse alopecia was noted from the age of 8 years: a skin biopsy revealed chronic in¯ammatory in®ltrates in the corium (Budka et al, 1976). Additionally, the coexistence of X-ALD and autoimmune endocrine disease has been reported in several patients (Federico et al, 1988;Dumic et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…At least three patients (D, I and Z) reported that the characteristic sparse scalp hair had already manifested itself before puberty. In fact, in the very ®rst report of a patient with AMN, ®rst areolar, then diffuse alopecia was noted from the age of 8 years: a skin biopsy revealed chronic in¯ammatory in®ltrates in the corium (Budka et al, 1976). Additionally, the coexistence of X-ALD and autoimmune endocrine disease has been reported in several patients (Federico et al, 1988;Dumic et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…50 years later Powers and Schaumburg [1] demonstrated characteristic inclusions in adrenal cortical cells ( Fig 1C) and in brain macrophages, which were then identified as saturated very long chain fatty acids (VLCFA) by Igarashi et al [2]. This led to the recognition that X-ALD is a metabolic disease and the identification of thousands of new patients with the various clinical phenotypes by the detection of increased VLCFA plasma levels [3][4][5]. X-linkage of this disease was first proposed on basis of a pedigree analysis by Fanconi et al 1963 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Adrenomyeloneuropathy (AMN) is a milder form of the disease, which manifests itself most commonly in the late twenties with spastic paraperesis in the lower extremities, sphincter and sexual dysfunction, and adrenal dysfunction. 9,10 Finally, there is a form of the disease that manifests itself by only adrenal cortical dysfunction. Women who are heterozygotes of the disease can also develop AMN in adulthood.…”
Section: Discussionmentioning
confidence: 99%